Respuesta :

Answer:

s = 10

r = -30

Step-by-step explanation:

Both expressions are equal to "r". You can substitute the first expression for into the second equation and replace "r".

r = r

-3s = 10 - 4s

To solve for the variable "s", keep it on the left side and more everything else to the right. When moving a number, use its reverse operation on the whole equation.

-3s + 4s = 10 - 4s + 4s        Add 4s to both sides.

-3s + 4s = 10          "4s" is cancelled out on the right, moved to the left

s = 10              Simplified the left side. Solved for "s"

To find "r", substitute s = 10 into the first equation.

r = -3s

r = (-3)(10)        Multiply

r = -30             Solved for "r"

Therefore the solution is when "s" is 10 and when "r" is -30.